2002
DOI: 10.1046/j.1365-2141.2002.03429.x
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 dysregulation in multiple myeloma: frequency and prognostic relevance

Abstract: Summary. The t(4:14) translocation affects two potential oncogenes, FGFR3 and MMSET, in multiple myeloma (MM). We investigated the frequency of FGFR3 dysregulation and its prognostic value in MM. FGFR3 mRNA levels were determined in 110 diagnostic bone marrow (BM) samples from MM patients. In addition, selected BM samples were screened for elevated MMSET mRNA levels. 14AE5% (16/110) of MM BM samples showed dysregulated FGFR3 expression.Follow-up of 76 MM patients showed no significant difference between FGFR3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Consistent with their results, Rasmussen et al (2002) also suggested that t(4;14)(p16.3;q32) is a monoclonal gammopathy of uncertain significance (MGUS)-to-myeloma transition event rather than a primary event, citing as support the lower prevalence of t(4;14)(p16.3;q32) in MGUS compared with multiple myeloma in some studies (Avet-Loiseau et al, 2002). This latter point is still controversial, as we have demonstrated a similar incidence of t(4;14)(p16.3;q32) in MGUS and myeloma using interphase FISH; it is, therefore, not clear that this abnormality represents a progression event.…”
Section: Mean Platelet Volume Is An Independent Risk Factor For Myocasupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with their results, Rasmussen et al (2002) also suggested that t(4;14)(p16.3;q32) is a monoclonal gammopathy of uncertain significance (MGUS)-to-myeloma transition event rather than a primary event, citing as support the lower prevalence of t(4;14)(p16.3;q32) in MGUS compared with multiple myeloma in some studies (Avet-Loiseau et al, 2002). This latter point is still controversial, as we have demonstrated a similar incidence of t(4;14)(p16.3;q32) in MGUS and myeloma using interphase FISH; it is, therefore, not clear that this abnormality represents a progression event.…”
Section: Mean Platelet Volume Is An Independent Risk Factor For Myocasupporting
confidence: 82%
“…Such a test would also allow the routine assessment of the antiplatelet effect of other drugs, like antihypertensives (e.g. in the studies cited by Endler et al, 2002) and lipid-lowering drugs (Milionis et al, 1999 Rasmussen et al (2002), showing no correlation between FGFR3 overexpression and clinical outcome in myeloma. This was surprising, as we have recently demonstrated by cytoplasmic immunoglobulin fluorescence in situ hybridization (cIg-FISH) a significantly shorter survival (26 vs 45 months, P < 0AE001) in myeloma patients having t(4;14) (p16.3;q32), (Fonseca et al, 2001).…”
Section: Mean Platelet Volume Is An Independent Risk Factor For Myocamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the specific clinical features of MM caused by individual chromosomal translocations and overexpressed genes are unclear. On the other hand, clinical observations have indicated that MM patients with t(11;14)(q13;q32) and translocation of CCND1 show a better prognosis (17)(18)(19), while MM patients with t(4;14)(q32.3;q32) and FGFR3 overexpression have a worse prognosis (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%